ANALISIS GAMBARAN KESIAPAN MASUK SEKOLAH DASAR SISWA-SISWI TAMAN KANAK-KANAK DI PEKANBARU - Lailatul Izzah; Riza Fitriana; Renny Rahmalia; Sepna Fanny Khairani; Indah Sarinah (JURNAL SENPLING MULTIDISIPLIN INDONESIA, 2025)
This reasearch aims to analyze the readiness of students for elementary school at Pembina 1 Kindergarten in Pekanbaru. The subjects were 112 group B students aged 5–6 years. The instrument used was the Nijmeegse Schoolbekwaamheids Test (NST), which measures cognitive aspects, concentration, language, instruction comprehension, motor skills, and emotional regulation. The results showed that 74 children (66.07%) were ready for school, 14 children (12.50%) were unsure/less ready, and 24 children (21.43%) were not ready for school. These findings indicate that the majority of children have adequate school readiness, although some still require additional support. This study provides practical implications for teachers, parents, and policymakers in improving children's readiness for elementary school.